2023
DOI: 10.1002/adfm.202213326
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin‐Based Biomimetic Membranes for Low Energy Water Desalination and Separation Applications

Abstract: The emergence of biomimetic materials developed using nature's inspiration and biological domains can drive a paradigm shift in the design and operation of future‐generation materials in separation applications. In recent years, biomimetic membranes have drawn interest of many researchers for water treatment applications. Among the biomimetic membranes, protein‐based membranes, specifically those synthesized by aquaporin, have received much attention in recent years due to their high osmotic water permeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 265 publications
0
7
0
Order By: Relevance
“…The discovery of human aquaporins pioneered the discovery of aquaporin orthologs in other species ranging from microbes to plants (Azarafza et al 2023 ). Microbial aquaporin genes have been identified in mollicutes, Gram-positive and negative bacteria, Archea, yeast, and mold.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of human aquaporins pioneered the discovery of aquaporin orthologs in other species ranging from microbes to plants (Azarafza et al 2023 ). Microbial aquaporin genes have been identified in mollicutes, Gram-positive and negative bacteria, Archea, yeast, and mold.…”
Section: Introductionmentioning
confidence: 99%
“…2 For example, membrane separation is the primary technology used in seawater desalination, with approximately 69% of the world's installed seawater desalination capacity and 85% of operational seawater desalination plants utilizing membrane separation. 6 However, limitations such as trade-off effect, poor stability, and inadequate antifouling properties are still challenges associated with membrane separation technology. 7 In nature, membrane separation also occurs in the cell with protein channels that enable the selective transport of molecules and ions across the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The diverse separation methods have led to membrane technology being widely applicable in ecological, biological, and chemical fields . For example, membrane separation is the primary technology used in seawater desalination, with approximately 69% of the world’s installed seawater desalination capacity and 85% of operational seawater desalination plants utilizing membrane separation . However, limitations such as trade-off effect, poor stability, and inadequate antifouling properties are still challenges associated with membrane separation technology …”
Section: Introductionmentioning
confidence: 99%
“…The frequent leakage of complex and recalcitrant oil resources has resulted in significant environmental damage, including the depletion of precious water resources and the destruction of eco-systems. , To address these challenges, superwetting membrane technology has been widely used in oil/water treatment due to its advantages of environmental protection, easy operation, and no secondary pollution . However, compared with superwetting membranes that lack a screening mechanism for small-sized droplets and exhibit poor separation efficiency, biomimetic materials with efficient removal of tiny droplets and selective superwettability have attracted people’s widespread attention. Such as, Ma et al reported PDMS/TA-Mn + /PI membrane by simulating the micronano structure on the surface of lotus effect and showed high flux and separation efficiency for various oil–water mixtures, which is attributed to its selective superwetting and submicron pore size . Inspired by the surface of cobweb-like nanostructure, Zhou et al designed a two-dimensional network nanostructure to reduce the average pore size of the membrane to achieve the screening effect on small droplets, which exhibited superhydrophilicity and underwater superoleophobicity .…”
Section: Introductionmentioning
confidence: 99%